'Surfacing' the politics of desire : literature, feminism, and myth - Vallury, Rajeshwari S. (Rajeshwari Suryamohan) (University of Toronto romance series (Unnumbered), 2008)
""Surfacing"" the Politics of Desire re-examines the ""myths"" of masculine desire in order to challenge this premise, placing literature at the centre of recent feminist debates over the ontology and politics of sexual difference.